Features of inclusive education with children with special educational needs in Uzbekistan - Abdullayeva Gavhar Saparovna (The Bioscan, 2024)
This article examines accessible educational resources and strategies for creating an inclusive learning environment for visually impaired and blind children in English language classes. It addresses key considerations for inclusive teaching, proposing a lesson model that integrates audio-lingual and communicative methodologies. The article also provides practical examples of classroom and extracurricular activities utilizing universal access system components and educational applications. These examples aim to support the learning of visually impaired students and serve as a valuable resource for educators seeking to enhance inclusivity in their classrooms.